An Evaluation of Certified Fraud Examiners’ Perceptions of Behaviour and Lifestyle Change as Fraud Indicators - Gichobi, Dennis M. (2014)
This is an exploratory and descriptive study that sought to investigate the perception of certified fraud examiners (CFEs) on the suitability of using red flag behaviour indicators to detect and investigate crime in Kenya. This was necessitated by the continued prevalence of fraud cases in government and private offices despite established mechanism for fraud detection and deterrence. The study used random sampling procedure to select 90 CFEs out of 150 CFEs who were ready to participate in this research. The study is anchored on social learning theory and self control theory. The study findings revealed that CFEs had an optimistic and positive perception towards the use of behavioral red flags as indicators for detecting fraud. Findings also showed that the CFEs believed that the indicators of lifestyle and behavior change can be used successfully for fraud identification in all the industries and occupations explored in the study. The study concluded that there is a need for further study on emerging trends of behavioural and lifestyle changes related to fraud commission. It also recommended that CFEs be proactive in monitoring and surveillance of suspect employees for tips on fraud. Keywords: Fraud, Fraud detection, Fraud investigation, Behavioural change, Keny